CLYDE SHELTON'S STRUGGLES TO PURSUE JUSTICE IN LAW ABIDING CITIZEN MOVIE - ALFADLY, MUCHAMMAD ANNAS (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Movie, Character and Characterization, Pursue Justice, Revenge, Psychological approach. Character is a part of movie. Characters are the people in narratives, and characterization is the author’s presentation and development of characters, is about Law Abiding Citizen movie that is analyzed by the writer is telling someone who pursues justice. The movie tells about someone who is disappointed with the law system which does not work properly, so he pursues justice. By the writer uses psychological approach to analyze main character in Law Abiding Citizen movie. The approach focuses on the concept of hatred and revenge. This studyaims to find out struggle of main character to pursue justice in Law Abiding Citizen movie.The result of the research shows that in Law Abiding Citizen movie, someone who is disappointed with the law system, struggles to pursue justice by any means to get justice and to change the law system to be better. For the next researchers who look for new object to be analyzed, they are suggested to use Law Abiding Citizen movie that is analyzed by using sociology theory, because this movie can be related to daily life.